Visitor Counter and Information Viewer at Photo Exhibitions using Embedded Systems and Web Services - I Made Bhaskara Gautama; I Gusti Ngurah Wikranta Arsa; Ni Putu Virgi Savita (Paradigma, 2022)
Photography is the art and production of images and light on a film or sensitized surface. It becomes a popular art as a hobby or for a living. Thus, many photography events are held such as photo exhibitions. The exhibition aims to show the work of art to the public or to promote the work so it can be profitable for the artist. One of the problems that arise from this photo exhibition is the need for the owner of the work or the event organizer to find out how many people have visited/seen a photo earnestly. This can be an indicator of public interest in the artwork. Counting manually is less effective to do considering the number of photos on display. Therefore, we need a tool that can be mass-produced at a relatively low cost to detect visitors to the photo site. The tool is based on a microcontroller (embedded system) which also uses the IoT concept. The tool is made using a NodeMCU microcontroller and PIR sensor. Based on the test results, the tool can count visitors with an accuracy rate of 82% and successfully displays information when visitors are detected and hides information when visitors leave the detection area.